ANALISIS KITAB RUJUKAN HADIS YANG DIGUNAKAN DALAM KITAB TA’LIM AL-MUTA’ALLIM OLEH SHAYKH AL-ZARNUJI - bin Kirin, Arwansyah; Masruri, Muhammad; bin Husen Ismail, Faisal; Marpuah, Siti (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2021)
Kitab Ta’lim al-Muta’alim yang dikarang oleh shaykh al-Zarnuji merupakan kitab klasik yang berisikan adab atau etika belajar dan mengajar antara guru dengan murid. Kitab ini cukup terkenal di Nusantara khususnya Indonesia, karena ia banyak dipelejari bahkan dijadikan rujukan di pondok-pondok pesantren sama ada yang klasik mahupun moden hingga ke hari ini. Hadis-hadis yang terdapat dalam kitab ini dirujuk dari pelbagai kitab sumber hadis. Namun sumber rujukan bagi kitab Ta’lim al-Muta’allim belum diterokai secara sistematik. Justeru kajian ini menerokai serta menganalisis sumber rujukan yang terdapat dalam kitab tersebut. Metodologi kajian ini adalah kualitatif melalui kaedah kepustakaan dan reka bentuk analisis kandungan kitab Ta’lim al-Muta’allim. Berdasarkan analisis yang dilakukan terhadap 40 hadis dan 108 riwayat, didapati 23 kitab yang diguna pakai oleh Shaykh al-Zarnuji dalam karyanya Ta’lim al-Muta’allim mulai dari kitab-kitab yang berisikan hadis-hadis Sahih sampailah kitab yang mengandungi hadis Da’if dan Mawdu’. Oleh itu, analisis tematik ini amat penting dilakukan agar dapat dikenal pasti kitab sumber hadis yang digunakan oleh Shaykh al-Zarnuji dalam karyanya Ta’lim al-Muta’allim.[Analysis of Hadith References Used in The Book Ta'lim Al-Muta'allim by Shaykh al-Zarnuji. The book of Ta'lim al-Muta'allim written by shaykh al-Zarnuji is a classic book which contains manners or ethics of learning and teaching between the teachers and students. This book is well-known in the archipelago, especially in Indonesia since it has been studied a lot and has even been used as a reference in Islamic boarding schools as well as classical and modern ones nowadays. The hadiths contained in this book are referred from various sources of hadith. However, the source of reference for the book of Ta'lim al-Muta'allim has not been recorded systematically. In fact, this study explores and analyzes the reference sources contained in the book. The methodology of this study is qualitative through literary principles and design forms of analysis of the content of the book Ta'lim al-Muta'allim. Based on the analysis carried out on 40 hadiths and 108 narrations, it was found that 23 books used by Shaykh al-Zarnuji in his Ta'lim al-Muta'allim started from books containing Sahih hadiths until the book containing the hadiths of Da ' if and Mawdu '. Therefore, this thematic analysis is very important to ensure that the source book of the hadiths used by Shaykh al-Zarnuji can be identified in his work Ta'lim al-Muta'allim.]